Age-Related Changes in the Ability to Switch between Temporal and Spatial Attention - Callaghan, Eleanor; Holland, Carol; Kessler, Klaus (Frontiers in Aging Neuroscience, 2017)
Background: Identifying age-related changes in cognition that contribute towards reduced driving performance is important for the development of interventions to improve older adults’ driving and prolong the time that they can continue to drive. While driving, one is often required to switch from attending to events changing in time, to distribute attention spatially. Although there is extensive research into both spatial attention and temporal attention and how these change with age, the literature on switching between these modalities of attention is limited within any age group. Methods: Age groups (21-30, 40-49, 50-59, 60-69 and 70+ years) were compared on their ability to switch between detecting a target in a rapid serial visual presentation (RSVP) stream and detecting a target in a visual search display. To manipulate the cost of switching, the target in the RSVP stream was either the first item in the stream (Target 1st), towards the end of the stream (Target Mid), or absent from the stream (Distractor Only). Visual search response times and accuracy were recorded. Target 1st trials behaved as no-switch trials, as attending to the remaining stream was not necessary. Target Mid and Distractor Only trials behaved as switch trials, as attending to the stream to the end was required. Results: Visual search RTs were longer on ‘Target Mid’ and ‘Distractor Only’ trials in comparison to ‘Target 1st’ trials, reflecting switch-costs. Larger switch-costs were found in both the 40-49 and 60-69 years groups in comparison to the 21-30 years group when switching from the Target Mid condition. Discussion: Findings warrant further exploration as to whether there are age-related changes in the ability to switch between these modalities of attention while driving. If older adults display poor performance when switching between temporal and spatial attention while driving, then the development of an intervention to preserve and improve this ability would be beneficial.